Democratic Republic of the Congo : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes recent developments in the financial system of the Democratic Republic of the Congo (DRC). It describes the monetary developments in 2003-05 and reform of the financial system. The paper examines the impact of monetary and exchange rate policies on inflation, including the nature of the lags involved. It reviews developments in the DRC's mining sector and mining's contribution to the economy from a fiscal perspective, showing a low effective level of taxation. The paper also discusses restructuring of the mining sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet